Comparative assessment of canine-origin Lactobacillus johnsonii CPN23 and dairy-origin Lactobacillus acidophillus NCDC 15 for nutrient digestibility, faecal fermentative metabolites and selected gut health indices in dogs. (31st July 2017) - Kumar, Sachin; Pattanaik, Ashok K.; Sharma, Shalini; Gupta, Reema; Jadhav, Sunil E.; Dutta, Narayan
Abstract: The present experiment was undertaken to validate a probiotic of canine origin for its potential use in dogs. A total of fifteen adult female Labrador dogs were allocated to three equal groups and fed a basal diet without probiotic (control) or with probiotic of either canine ( Lactobacillus johnsonii CPN23; cPRO) or dairy ( L. acidophilus NCDC 15; dPRO) origin for 9 weeks. The digestibility of most macronutrients remained similar among the groups; however, fibre digestibility was improved ( P  = 0·034) in dogs receiving cPRO. The faecal fermentative metabolites ammonia ( P   <  0·05) and lactate ( P  = 0·094) were altered favourably, indicating a positive influence of both probiotics. Faecal concentrations of acetate, propionate and butyrate were increased ( P   <  0·01) in both probiotic groups. However, improvements were higher in cPRO v . dPRO. The delayed-type hypersensitivity reaction to intradermal inoculation of phytohaemagglutinin-P was higher ( P  = 0·053) in cPRO as compared with control. The antibody response to sheep erythrocytes was, however, similar across the three groups. Overall, in dogs, the canine-origin probiotic was superior when compared with the dairy-origin probiotic.